Delayed tension pneumothorax 2 days after shoulder arthroscopic rotator cuff repair: a case report - Yuan Li; Ke He; Ju Wu; Guan-Jun Sun; Yi Yin; Xu Peng (BMC Musculoskeletal Disorders)
Abstract Background The report of tension pneumothorax after shoulder arthroscopy is very rare, and it is easy to be misdiagnosed and missed clinically, thus delaying the treatment of patients and endangering their lives. Case presentation A 68-year-old woman was admitted to the joint surgery department. Chief complaint: left shoulder joint pain with limited movement for 6 months. Physical examination: lateral acromial tenderness (+), significant shoulder tenderness, Job sign (+), Hapolen sign (+), Lift off sign (+), forward flexion about 80°, abduction about 80°, external rotation about 30°, internal buckle and hip level. Magnetic resonance imaging(MRI) revealed a tear of the left supraspinatus muscle and edema in the rotator cuff space. Left rotator cuff repair and joint capsule release under arthroscope in lateral position were arranged for the patient. The patient’s vital signs were stable during the operation and she returned to the ward safely. At 13:27 PM on the second day of the operation, sudden shortness of breath, sweating, poor spirit, able to respond to breathing, able to act as instructed, shortness of breath, both lungs and sporadic dry and wet rale, heart rhythm, not heard and obvious pathological murmurs were immediately treated with mask oxygen inhalation and sputum aspiration, and a small amount of white frothy sputum could be aspirated. Please consult the intensive care department immediately. Subsequently, the Peripheral oxygen saturation. (SPO2) of the patient gradually decreased to 60%, and the patient was lethargic and given balloon assisted ventilation, the oxygen saturation remained between 57% and 65%. The patient’s vital signs were stable after immediate emergency treatment with endotracheal intubation. A physical examination on ward round the next morning revealed fullness of the chest and widening of the thorax. Tympanic sound was found on right thoracic percussion, but no respiratory sound was found on auscultation. The diagnosis was tension pneumothorax. The cardiothoracic surgeon immediately performed closed thoracic drainage in the third intercostal space on the right midline of the clavicle with a 20-gauge needle. Two days later, the right lung returned to normal. There was no lung discomfort during the six-month follow-up. She has returned to her pre-injury athletic level. Conclusion Delayed tension pneumothorax after arthroscopic rotator cuff repair is a very rare condition with no clear cause. Special attention should be paid to patients with sudden dyspnea after shoulder arthroscopy, and early diagnosis and treatment should be conducted according to the symptoms, signs and imaging examinations of patients to avoid misdiagnosis and missed diagnosis.